Pengaruh Manajemen Kinerja terhadap Kepuasan dan Retensi Karyawan di Era Digital di Yayasan Perguruan Kampus Padangsidimpuan - Silviana Batubara; Ade Maya Mei Shanty; Makhrani Makhrani (Journal on Education, 2025)
This study aims to analyze the effect of performance management on employee satisfaction and retention at Yayasan Perguruan Kampus Padangsidimpuan in the context of the digital era. The study used a quantitative method with a survey approach to 60 employees. Data were analyzed using multiple regression to test the direct effect and the Sobel test to identify the mediating role of employee satisfaction. The results showed that performance management has a positive and significant effect on employee satisfaction (β = 0.532; p = 0.000) and employee retention (β = 0.521; p = 0.000). In addition, employee satisfaction was found to act as a significant mediator in the relationship between performance management and employee retention (z = 3.52; p = 0.000). This study also highlights the importance of implementing a transparent, fair, and responsive technology-based performance management system in improving employee welfare and loyalty. The results of this study provide practical implications for organizations, especially in developing a performance management system that focuses not only on work results, but also on employee development. In addition, this study recommends the need for continuous evaluation of the performance management system in the organization to improve retention and minimize employee turnover.